EVALUASI DETERMINAN KEPUASAN MAHASISWA - Santoso, Aprih; Kusnilawati, Nunik (FEB Universitas Sam Ratulangi Manado, 2020)
A college as a service company in carrying out business activities or educational activities, generally what must be considered is the orientation towards consumers, which concerns what companies must satisfy their consumers. In service companies, especially higher education institutions that are consumers are students, with more attention to aspects of customer orientation, of course, the goals to be achieved by the company will be realized. Problems that occur at the University of â€œXâ€ make students feel dissatisfied and this causes complaints or complaints, including: inadequate parking, campus websites that are often slow, completeness of damaged facilities and infrastructure, administrative services that tend to be long.The purpose of this study is to examine and analyze the effect of service quality and university reputation on student satisfaction, with trust as a mediating variable. The population in this study were students from University â€œXâ€ enrolled in the odd semester 2019/2020 Study Plan Card (KRS) of 22,753 students. The number of samples in this study were 99.56 students rounded up to 100 students (based on the Slovin formula). The analysis was carried out with the help of the SPSS program. The variable relationship model will be analyzed by path analysis. The result of research show service quality and university reputation have a direct effect on student trust at Universityof â€œXâ€. Service qualityand university reputation have a direct effect on student satisfaction at University of â€œXâ€. Trust has a direct influence on student satisfaction at the University of â€œXâ€.Â Keywords: Â Trust, Service Quality, Reputation, Satisfaction